Last updated at March 16, 2017 by Teachoo

Transcript

Ex 2.4, 4 Factorise: 12x2 − 7x + 1 12x2 − 7x + 1 We factorize using the splitting the middle term method = 12x2 − 4x − 3x + 1 = 4x (3x − 1) − 1 (3x − 1) = (3x − 1) (4x − 1) Ex 2.4, 4 Factorise: (ii) 2x2 + 7x + 3 2x2 + 7x + 3 We factorize using the splitting the middle term method = 2x2 + 6x + x + 3 = 2x (x + 3) + 1 (x + 3) = (x + 3) (2x+ 1) Ex 2.4, 4 Factorise: (iii) 6x2 + 5x − 6 6x2 + 5x − 6 We factorize using the splitting the middle term method = 6x2 + 9x − 4x − 6 = 3x (2x + 3) − 2 (2x + 3) = (2x + 3) (3x − 2) Ex 2.4, 4 Factorise: (iv) 3x2 − x − 4 3x2 − x − 4 We factorize using the splitting the middle term method = 3x2 − 4x + 3x − 4 = x (3x − 4) + 1 (3x − 4) = (3x − 4) (x + 1)

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He provides courses for Mathematics from Class 9 to 12. You can ask questions here.